16 A randomised controlled trial of deep brain stimulation in obsessive compulsive disorder: a comparison of ventral capsule/ventral striatum and subthalamic nucleus targets. Issue 8 (13th July 2017) - Tyagi, Himanshu; Zrinzo, Ludvic; Akram, Harith; Apergis-Schoute, Annemieke; Drummond, Lynne; Fineberg, Naomi; Foltynie, Thomas; Jahanshahi, Marjan; Limousin, Patricia; Matthews, Keith; Robbins, Trevor; Rothwell, John; et al.
Abstract : Objective: Obsessive compulsive disorder (OCD) has a lifetime prevalence of 1%–2%. Standard treatments are ineffective in up to 40% of cases. Even with the best treatments, there remains a subgroup with severe symptoms and significant disability. Studies of deep brain stimulation (DBS) for OCD have shown improvement in both symptoms and quality of life in severe OCD. Two targets in particular have shown promise: the anteromedial subthalamic nucleus (STN) and the ventral capsule/ventral striatum (VC/VS). 1–3 It is not clear however if one site has advantages over the other and, with regard to the VC/VS site, whether stimulation of the anterior capsule white matter or ventral striatum/nucleus accumbens grey matter is critical for improvement. 2, 3 We report a within subject comparison of the effect of DBS on OCD symptoms at STN and VC/VS sites both individually and together (ClinicalTrials.gov #NCT02655926 ). The aims of the study were to determine: a) the efficacy of DBS at each site; b) whether stimulation of both sites improves the response compared to either site alone; and c) the critical stimulation contacts at the VC/VS site. Method: Six participants, with severe treatment refractory OCD, were recruited via the UK specialist OCD service and underwent implantation of bilateral electrodes at both the VC/VS and anteromedial STN sites. A Leksell frame-based MRI-guided and MRI-verified approach under general anaesthesia was used. The subthalamic nucleus was localised on axial T2-weighted stereotactic images and the VC/VS localised on coronal and axial proton density images (Siemens, 1.5T). Using a double blind cross-over design, 12 weeks stimulation at STN and VC/VS sites was compared, followed by stimulation at both sites for 12 weeks. The primary outcome measure was YBOCS: an improvement of greater than or equal to 35% was the predefined response. Results: Accurate stereotactic and anatomical lead location was confirmed on immediate postoperative stereotactic MR images in all patients. For the VC/VS target, the deepest DBS lead contact was within the nucleus accumbens, the one superior to that in the "shell" of the nucleus accumbens while the superior two contacts were within the inferior aspect of the anterior limb of the internal capsule. The response rates (defined as the number of patients with >35% reduction in YBOCS) were: STN 3/6; VC/VS: 5/6; STN + VC/VS: 5/6. In the one non-responder YBOCS reduction was 32% after the combined STN+VC/VS stimulation phase. For the whole group, the mean reduction in YBOCS scores were: STN 16.3; VC/VS: 19.2; STN + VC/VS: 22.0 which represents a mean reduction of 42%, 53%, 62% from their own baseline scores and a reduction to predefined mild/subclinical symptoms of 0%, 50% 50% respectively. The top two DBS contacts of the quadripolar lead were found to be the most effective at the VC/VS target in all 6 patients. Conclusions: These results suggest that: a) The VC/VS site may be superior to the STN site for the amelioration of severe OCD symptoms; b) There is only a modest advantage of stimulating both sites together; and c) The effective stimulation site for the VC/VS target is the inferior aspect of the anterior limb of the internal capsule and not the ventral striatum/nucleus accumbens grey matter. Additional Info The study was funded by the MRC (MR/J012009/1). References: . Mallet, et al. N Eng J Med 2008;359:2121. . Denys, et al. Arch Gen Psychiatry2010;6:1061. . Greenberg, et al. Molecular Psychiatry2010;15:64.